2007
DOI: 10.1186/1472-6807-7-71
|View full text |Cite
|
Sign up to set email alerts
|

The structure of mollusc larval shells formed in the presence of the chitin synthase inhibitor Nikkomycin Z

Abstract: Background: Chitin self-assembly provides a dynamic extracellular biomineralization interface. The insoluble matrix of larval shells of the marine bivalve mollusc Mytilus galloprovincialis consists of chitinous material that is distributed and structured in relation to characteristic shell features. Mollusc shell chitin is synthesized via a complex transmembrane chitin synthase with an intracellular myosin motor domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 57 publications
2
64
0
1
Order By: Relevance
“…We also speculate that elevated seawater CO 2 influenced biological processes responsible for larval shell calcification. In a study of molecular mechanisms of larval shell formation, Weiss & Schönitzer (2006) demonstrated the presence of chitinous material in the larval shell of M. galloprovincialis; in a subsequent study, Schönitzer & Weiss (2007) showed that larval shell formation was radically impaired by treatment of the M. galloprovincialis larvae with a chitin synthesis inhibitor, Nikkomycin Z. Observed types of larval shell malformation at the organism scale included asymmetry of the 2 shell valves, reduced size, shell undulation, and convex hinge, which are similar to our observations in high-CO 2 exposed embryos.…”
Section: Discussionmentioning
confidence: 99%
“…We also speculate that elevated seawater CO 2 influenced biological processes responsible for larval shell calcification. In a study of molecular mechanisms of larval shell formation, Weiss & Schönitzer (2006) demonstrated the presence of chitinous material in the larval shell of M. galloprovincialis; in a subsequent study, Schönitzer & Weiss (2007) showed that larval shell formation was radically impaired by treatment of the M. galloprovincialis larvae with a chitin synthesis inhibitor, Nikkomycin Z. Observed types of larval shell malformation at the organism scale included asymmetry of the 2 shell valves, reduced size, shell undulation, and convex hinge, which are similar to our observations in high-CO 2 exposed embryos.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments showed that chitin synthesis is closely linked to cell division, the development of tissues and organs, and the overall symmetry of the body plan. This explains to some extent, why in the particular case of mollusc larval shell development, the presence of tiny amounts of the chitin synthase inhibitor NikkomycinZ during growth prevented proper shell formation on different levels of hierarchy [135].…”
Section: Myosin Chitin Synthases and Biomineralizationmentioning
confidence: 99%
“…Surprisingly, they were still alive and active. The shell remnants were irregular, sensitive to etching by water and mechanically instable [64,135].…”
Section: Encoding Mollusc Shell Structurementioning
confidence: 99%
See 2 more Smart Citations